The Efficacy of Aroma and Music Therapy to Reduce Dental Anxiety and Pain Intensity - Zainab Waheed, Mahnoor Imran, Fatima Liaqat, Maidah Aziz, Hira Butt, Sajid Ali Khan (Pakistan Journal of Medical & Health Sciences, 2022)
This study aimed to determine the effectiveness of aromatherapy and music therapy in managing dental anxiety and pain among restorative dental patients in Peshawar, Pakistan. Sixty dental patients were selected after strictly following the inclusion and exclusion criteria. Informed consent was taken from the patients and instructed on the study protocols. Two groups were formed. One group had aromatherapy during the dental procedure, and the other had music therapy. The dental anxiety scale revised, present pain intensity and pain severity were used as the measuring tools in the study. SPSS 23 was used for statistical analysis. Chi-square and Mann-Whitney U tests were used for the analysis of the results. The association between pain intensity of dental patients with aromatherapy and music therapy was not significant. The percentage of discomforting pain in patients after aromatherapy was higher than in music therapy, while a higher percentage of patients were completely pain-free after music therapy. The mean rank score of pain severity was higher in a patient who received aromatherapy than music therapy. The difference in the pain severity scores across the therapy groups was statistically significant. The mean rank score of dental anxiety was also statistically significantly different across the therapy groups. The mean rank score of dental anxiety was higher for the patients who received aromatherapy than music therapy. It was concluded that distraction therapy works better to reduce the dental anxiety and pain intensity of dental patients. Furthermore, studies should be conducted to closely evaluate the difference and association of non-pharmacological treatments in this area.